The Role of Body Image Satisfaction in Predicting Enjoyment of Physical Education: A Correlational Study of Secondary School Adolescents - Adianto, Muhammad Rifki; S, Adi (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2026)
Body image has become a salient psychological factor influencing adolescents’ experiences in physical education (PE), particularly in environments where physical appearance and performance are socially visible. Although PE is intended to promote positive engagement and enjoyment, concerns about body image may shape students’ affective responses during participation. Therefore, this study aims to examine the relationship between body image satisfaction and enjoyment in physical education among students. This study employed a quantitative correlational design using a nonparametric approach. A total of 364 students from several schools participated in the study. Data were collected using the Physical Activity Enjoyment Scale (PACES) to measure enjoyment and a 5-point Likert-scale questionnaire to assess body image satisfaction. Normality tests indicated non-normal data distribution (p < 0.05); therefore, Spearman’s rho correlation analysis was used. The results revealed a statistically significant negative relationship between body image satisfaction and enjoyment in physical education (ρ = -0.27, p < 0.05). Although significant, the correlation was weak, indicating that body image satisfaction is not the primary determinant of students’ enjoyment. This finding suggests that students’ emotional experiences in PE are influenced by more complex psychological and social processes, including social comparison and perceived evaluation within the learning environment. In conclusion, enjoyment in physical education is not solely shaped by body image satisfaction but also by pedagogical and social factors. These findings highlight the importance of creating inclusive, supportive, and non-evaluative learning environments to enhance students’ comfort and enjoyment during physical activity.